PELAKSANAAN HAK MEMILIH DALAM PEMILU BAGI PENYANDANG DISABILITAS INTELEKTUAL DI KOTA SAMARINDA DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Vitrya Lestari P; Hudali Mukti (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Constitutional Court Decision Number. 135/PUU-XIII/2015 states that citizens who are mentally/memory impaired can still participate in general election contestation. However, in reality, there are still many mentally disabled persons who are considered incompetent and unable to use their right to vote in elections. This is what later became the author's interest in discussing the Implementation of Voting Rights in Elections for People with Mental Disabilities, especially in Samarinda City. The author's research objective in conducting this research was to find out how the implementation and constraints faced in exercising the right to vote. The type of research used in this thesis is empirical juridical. Currently, people with mental disabled have enough awareness to participate in elections. However, the involvement of persons with mental disability to use their right to vote is limited to used their right to vote. Obstacles that occur in the use of the right to vote for persons with Mental Disabilities, there are: the problem of not specifically classifying Persons with Mental Disabilities, the absence of active communication from Persons with Mental Disabilities, the process of matching and researching data is not optimal, and the lack of delivery of electoral information. In overcoming these obstacles, the General Election Comissions seeks to form a Democratic Volunteer (Relations) using a door to door system.